Challenges of Small- and Medium-Sized Enterprises (SMEs) in Business Growth: A Case of Footwear Industry. Issue 1 (June 2021) - Islam, A. K. M. Hedaitul; Sarker, Md. Rayhan; Hossain, Md. Israil; Ali, Kauser; Noor, K. M. Asadun
Small- and medium-sized enterprises (SMEs) create more employment opportunities and thus, contribute to the national economy of a country. Footwear SMEs have been identified as an emerging economy in Bangladesh, which is facing several challenges. Very few studies focused on the challenges of SMEs' business growth. However, until now, no literature particularly focused on the challenges of footwear SMEs and discussed how to tackle these challenges. To fill this research gap, we use the Fuzzy Delphi Method and fuzzy analytical hierarchy process, to find out the degree of importance of critical challenges of footwear SMEs. In our study, 16 critical challenges are identified among which lingering in cash flow (F3), fierce market competition (E1), access to finance (F2), unfavorable bank loan policy (F1), and poor supply chain management (E2) have been ascertained as the top five critical challenges, respectively. This study contributes to the existing literature of SMEs by identifying five new challenges from the context of the footwear industry. Furthermore, we suggest some possible measures to overcome the identified challenges. This study can guide the government, practitioners, and SME policymakers to address these challenges for the growth of any SME sector.